Leftist, Jewish, and Canadian Identities Voiced in the Repertoire of the Toronto Jewish Folk Choir, 1939-1959 - Wolters-Fredlund, Benita (MUSICultures, 2002)
This article focuses on a twenty-year period of the Toronto Jewish Folk Choir, during which the ensemble was conducted by Emil Gartner. Considering historical contexts, including political pressures and social frameworks, the author shows how repertoire choices were linked to overlapping patterns of identity, notably the choir as a voice for progressive political ideas, as a Jewish community group, and as a player in the emerging multicultural Canadian fabric.